Systems thinking for hygiene in settings with high risk of infectious disease transmission - Freeman, M.C.; Crocker, J.; Chipungu, J.; Bagwan, J.; Dione, Michel M.; Dreibelbis, R.; Dumlao, M.C.; Faruque, A.S.G.; Flint-O'Kane, M.; Gautam, O.P.; Lakhe, N.A.; Muga, R.; et al. (Nature Water, 2025)
Hygiene is critical for controlling infectious disease and delivering well-being. During the pandemic phase of COVID-19, there was widespread awareness of the importance of hygiene for disease control, and demand was high for action to improve access to hygiene materials. However, those efforts have faltered, and, in general, interventions to improve hygiene at scale have shown limited success in delivering sustained behaviour change and health impact. We convened experts in hygiene across sectors (for example, health, education and agriculture) and disciplines (for example, academia, policy and practice) in Dakar, Senegal, to discuss the critical barriers and opportunities for researching, developing and implementing systems-level hygiene interventions and promote learning across sectors, with a focus on systems approaches. We report what is needed to achieve catalytic improvements in hygiene in low-income settings and the Global South, with an emphasis on ‘hygienic systems’ that target all relevant hygiene moments—a set of associated behaviours at a given time and place with high pathogen exposure risk—and their enabling conditions and pre-conditions. This focus beyond individual behaviours will require removing silos across sectors and ministries, the generation of relevant evidence for policymakers and the localization of guidance.